Electrochemical treatment of aquaculture wastewater effluent and optimization of the parameters using response surface methodology - Bhatt, Pankaj; Huang, Jen-Yi; Shivaram, Karthik B.; Brown, Paul; Yakamercan, Elif; Simsek, Halis (Elsevier Sci Ltd, 2023)
The electrocoagulation (EC) and electrooxidation (EO) processes are employed widely as treatment processes for industrial, agricultural, and domestic wastewater. In the present study, EC, EO, and a combination of EC + EO were evaluated as methods of removing pollutants from shrimp aquaculture wastewater. Process parameters for electrochemical processes, including current density, pH, and operation time were studied, and response surface methodology was employed to determine the optimum condition for the treatment. The effectiveness of the combined EC + EO process was assessed by measuring the reduction of targeted pollutants, including dissolved inorganic nitrogen species, total dissolved nitrogen (TDN), phosphate, and soluble chemical oxygen demand (sCOD). Using EC + EO process, more than 87% reduction was achieved for inorganic nitrogen, TDN, and phosphate, while 76.2% reduction was achieved for sCOD. These results demonstrated that the combined EC + EO process provided better treatment performance in removing the pollutants from shrimp wastewater. The kinetic results suggested that the effects of pH, current density, and operation time were significant on the degradation process when using iron and aluminum electrodes. Comparatively, iron electrodes were effective at reducing the half-life (t1/2) of each of the pollutants in the samples. The application of the optimized process parameters on shrimp wastewater could be used for large-scale treatment in aquaculture.
Keywords: Shrimp wastewater; Electrocoagulation; Electrooxidation; Electrochemical methods